Nanoimprint glue for electronic semiconductor manufacturing and preparation method thereof
Patent Information
- Application Number
- CN202611151183.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
目前,尚未有将动态共价键与无机纳米刚性骨架协同设计以同时抑制收缩和释放应力的报道
本发明提供了一种用于电子半导体制造的纳米压印胶,通过引入可聚合配体修饰的四脚状半导体量子点及二硒键动态化学设计,在光固化过程中实现了对纳米压印胶体积收缩、内应力、脱模行为及填充性能的协同调控。具体机制如下:
Smart Images

Figure SMS_3 
Figure SMS_5 
Figure SMS_8
Abstract
Description
Technical Field
[0001] This invention relates to the field of photosensitive materials technology, specifically to a nanoimprint adhesive for electronic semiconductor manufacturing and its preparation method. Background Technology
[0002] Nanoimprint lithography (NIL) technology directly transfers micro- and nano-patterns from a template to an imprinting layer via mechanical imprinting, avoiding the diffraction limit problem of optical lithography. It boasts advantages such as high resolution, low cost, and high yield, and has been listed as one of the key next-generation patterning technologies in the international device and system roadmap. However, the industrial application of nanoimprint lithography is still limited by the performance defects of the imprinting adhesive materials themselves, with curing shrinkage and demolding stress being the two most prominent bottlenecks.
[0003] Regarding curing shrinkage, conventional acrylic imprinting adhesives exhibit a volume shrinkage rate as high as 5%-10% during UV curing. This leads to errors in pattern linewidth, rough edges, and the accumulation of internal stress within the adhesive layer. The shrinkage stress is released during demolding, causing pattern drift and affecting the stacking accuracy of multilayer imprints. Existing technologies, through methods such as introducing ring-opening polymerization of cyclic monomers (e.g., alicyclic epoxides), adding inorganic nanofillers (e.g., SiO2, TiO2), or using hyperbranched polymers, have reduced the shrinkage rate to the 3%-5% range. However, this is insufficient to meet the accuracy requirements of nodes with linewidths below 50nm, and it fails to address the secondary stress damage problem during demolding.
[0004] Regarding demolding performance, the strong adhesion between the imprinting adhesive and the template results in excessive demolding force, causing rapid wear of the anti-adhesion layer (usually a fluorosilane monolayer) on the template surface, with an effective service life of only a few dozen cycles. To improve demolding, existing technologies mainly employ two strategies: one is fluorination treatment of the template surface, and the other is adding fluorinated or silicone-containing lubricants to the imprinting adhesive. However, these methods are all static interface modifications, which cannot eliminate curing internal stress, and the lubricants are prone to migration and loss. In recent years, dynamic covalent bonds (such as disulfide bonds and thiocarbamate bonds) have been used for stress release in photocurable materials, but their triggering temperatures are high or overlap with the wavelength of ultraviolet curing light, making it difficult to achieve stepwise control in NIL room temperature processes. Although mercapto ligand exchange has become a routine technique in this field (such as CN120025812A), which can achieve stable dispersion and covalent anchoring of quantum dots in polar solvents, existing research is limited to using quantum dots as static fillers or luminescent centers, without addressing the synergistic use of their rigid framework and dynamic covalent bonds for stress management. Currently, there are no reports of co-designing dynamic covalent bonds with inorganic nano-rigid frameworks to simultaneously suppress contraction and release stress.
[0005] Based on this, the present invention provides a nanoimprint adhesive for electronic semiconductor manufacturing and its preparation method. By introducing polymerizable ligand-modified semiconductor quantum dots into a crosslinkable resin matrix, the surface of the quantum dots is covalently bonded with polymerizable ligands containing diselenylene bonds (-Se-Se-). Its rigid inorganic core inhibits the macroscopic shrinkage of the crosslinked network during the ultraviolet curing stage. At the same time, the diselenylene bonds undergo a reversible exchange reaction under visible light triggering to release the curing internal stress, in order to achieve the comprehensive technical effects of ultra-low volume shrinkage rate, improved high aspect ratio filling performance, extended template life and reduced demolding defect rate. Summary of the Invention
[0006] Therefore, the present invention provides a nanoimprint adhesive for electronic semiconductor manufacturing and a method for preparing the same, in order to overcome the shortcomings of the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a nanoimprinting adhesive for electronic semiconductor manufacturing is provided, comprising the following raw materials in parts by weight: 40-60 parts of crosslinkable resin containing double bonds; 8-20 parts of polymerizable ligand-modified semiconductor quantum dots; 15-40 parts of reactive diluent; 1-5 parts of photoinitiator; 10-25 parts organic solvent.
[0008] Furthermore, the polymerizable ligand-modified semiconductor quantum dot comprises: Semiconductor quantum dots, and Polymerizable ligands covalently bonded to their surface.
[0009] Furthermore, the general structural formula of the polymerizable ligand is as follows: CH2=C(CH3)-C(O)-O-(CH2) n -Se-Se-(CH2) m -SH; Where n = 2 - 6, m = 2 - 6, and n and m are both integers.
[0010] Furthermore, n = 2 - 4, m = 2 - 4, where n and m are both integers.
[0011] Furthermore, the semiconductor quantum dot is a four-legged quantum dot.
[0012] Furthermore, the tetrapod quantum dot is selected from at least one of group II-VI semiconductor tetrapod quantum dots and group III-V semiconductor tetrapod quantum dots.
[0013] Furthermore, the quadrupedal quantum dot is a group II-VI semiconductor quadrupedal quantum dot, which includes, but is not limited to, quadrupedal CdSe quantum dots.
[0014] Further, the crosslinkable resin containing double bonds is selected from at least one of bisphenol A epoxy acrylate and phenolic epoxy acrylate; the reactive diluent is an acrylate reactive diluent, which includes, but is not limited to, trimethylolpropane triacrylate (TMPTA); the organic solvent is selected from at least one of alcohol ether organic solvents, ester organic solvents, and ketone organic solvents; the photoinitiator is selected from at least one of acylphosphine oxide photoinitiators, α-hydroxy ketone photoinitiators, α-amino ketone photoinitiators, aromatic ketone photoinitiators, and thioxanthone photoinitiators.
[0015] Furthermore, the organic solvent is an alcohol ether organic solvent, including but not limited to propylene glycol methyl ether acetate (PGMEA); the photoinitiator is an acylphosphine oxide photoinitiator, including but not limited to phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0016] According to a second aspect of the present invention, a method for preparing nanoimprint adhesive for electronic semiconductor manufacturing is provided, comprising the following steps: S1. Preparation of polymerizable ligand-modified semiconductor quantum dots; S2. Under light-protected conditions, the polymerizable ligand-modified semiconductor quantum dots from step S1 are ultrasonically dispersed in an organic solvent to form a quantum dot pre-dispersion. S3. Add crosslinkable resin containing double bonds, reactive diluent and photoinitiator sequentially to the quantum dot predispersant formed in step S2, stir and mix evenly; after vacuum degassing and filtration, obtain nanoimprint adhesive.
[0017] The method of using the nanoimprint adhesive is as follows: (1) The substrate was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, dried with nitrogen and then treated with oxygen plasma at a power of 40-60W for 1-3 minutes. (2) Spin coat the nanoimprint adhesive onto the substrate at a speed of 1000-2000 r / min for 30-90 s, with a layer thickness of 150-200 nm. Then bake it on a hot plate at 80-90℃ for 90-120 s to remove the organic solvent. (3) Align the template with the micro-nano structure pattern with the substrate coated with imprinting adhesive, apply a pressure of 1-3 bar, and hold the pressure for 30-90 seconds; (4) Curing by ultraviolet light irradiation under an inert gas atmosphere; (5) Vertically lifting the template separates the template from the imprinting adhesive, thus obtaining a nanoimprint pattern; (6) Post-curing with visible light to obtain cured adhesive film material; The curing parameters are: wavelength 365nm, light intensity 40-60mW / cm². 2 Light exposure time: 10-30 seconds; The vertical lifting template has a lifting speed of 0.1-0.2 mm / s; The post-curing parameters are: wavelength 405-450nm, light intensity 20-40mW / cm². 2 The illumination time is 30-90 seconds.
[0018] Furthermore, the method for preparing polymerizable ligand-modified semiconductor quantum dots is as follows: Oleic acid-terminated semiconductor quantum dots were dispersed in anhydrous ethanol under an inert gas atmosphere. The pH of the system was adjusted to 5.0-6.5, polymerizable ligands and antioxidants were added, and the reaction was carried out at 50°C in the dark for 12-24 hours with stirring. After precipitation with acetone, centrifugation, redispersion and purification with toluene, and vacuum drying, polymerizable ligand-modified semiconductor quantum dots were obtained.
[0019] Furthermore, the mass ratio of semiconductor quantum dots to polymerizable ligands is 100:(3-8); the amount of antioxidant added is 0.01wt.%-0.1wt.%.
[0020] Furthermore, the mass ratio of the semiconductor quantum dot to the polymerizable ligand is 100:5; the amount of antioxidant added is 0.01wt.%-0.05wt.%.
[0021] Furthermore, the antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol (BHT), 4,4'-butylene-bis(6-tert-butyl-3-methylphenol) (BBM), antioxidant 1726, and antioxidant 1010.
[0022] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol (BHT).
[0023] Furthermore, the parameters for ultrasonic dispersion in step S2 are as follows: ultrasonic power 100-200W, time 20-40min.
[0024] Furthermore, the parameters for uniform mixing in step S3 are as follows: rotation speed 800-1200 r / min, time 30-60 min.
[0025] Furthermore, the inert gas includes, but is not limited to, nitrogen.
[0026] According to a third aspect of the present invention, the application of the nanoimprint adhesive prepared by the said preparation method in electronic semiconductor manufacturing is provided.
[0027] The present invention has the following advantages: This invention provides a nanoimprint liner for electronic semiconductor manufacturing. By introducing polymerizable ligand-modified tetrapod semiconductor quantum dots and a dynamic chemical design of diselenyl bonds, the volume shrinkage, internal stress, demolding behavior, and filling performance of the nanoimprint liner are synergistically controlled during photocuring. The specific mechanism is as follows: (1) Polymerizable ligand-modified semiconductor quantum dots (such as polymerizable ligand-modified tetrapod CdSe quantum dots) are covalently anchored in the cross-linked network through polymerizable ligands. During UV curing, the rigid inorganic core of the polymerizable ligand-modified semiconductor quantum dots does not undergo volume change, and its four-arm branched structure penetrates the network to form a three-dimensional mechanical constraint, directly resisting the macroscopic shrinkage of the polymer from a physical perspective. At the same time, the diselenide bonds anchored to the surface of the quantum dots trigger a reversible exchange reaction under visible light (405-450nm) irradiation, causing local topological rearrangement of the cross-linked network, uniformly releasing the internal stress accumulated during curing, and further suppressing the apparent shrinkage caused by stress concentration. The two mechanisms work synergistically to keep the curing shrinkage rate at a low level.
[0028] (2) After curing and before demolding, visible light (405-450nm) is applied to trigger a reversible exchange reaction of diselenylene bonds. This reaction causes topological rearrangement of the cured network without changing the total crosslinking density (gel content remains above 95%), and releases the internal stress accumulated during curing and imprinting in a uniform manner. The elimination of internal stress significantly reduces the adhesion between the adhesive film and the template, changing the demolding process from peeling to separation, and the demolding force is greatly reduced. At the same time, the demolding interface avoids resin residue and wear of the anti-adhesive layer, and the number of times the template can be reused is significantly increased.
[0029] (3) Visible light triggering of diselenylene bonds releases the curing internal stress, thereby significantly reducing the concentrated stress on the film during demolding and avoiding structural defects such as pattern tearing and edge burrs caused by stress concentration. At the same time, the reduction in demolding force reduces the risk of particle contamination caused by residue falling off the template surface. The elimination of curing internal stress significantly inhibits the generation of repetitive defects, which, once formed, tend to reappear in multiple imprints of the same template and are one of the key factors affecting the yield of nanoimprinting.
[0030] (4) The unique three-dimensional branched structure of tetrapod quantum dots can induce a confinement-induced packing frustration in polymer melts, meaning that polymer chains cannot enter the void regions inside the tetrapods, generating entropy costs, thereby increasing chain mobility and significantly reducing the effective viscosity of the system without compromising the thermal and mechanical integrity of the material. This effect enables colloids to efficiently fill nanopores with an aspect ratio of 3:1, significantly reducing the occurrence of bubbles or void defects.
[0031] (5) The visible light triggering wavelength (405-450 nm) of the diselenide bond does not overlap with the ultraviolet curing wavelength (365 nm) in the spectrum, allowing the two steps of ultraviolet curing to lock the pattern and visible light triggering to release stress to be completed sequentially and independently on the same process platform. The photoinitiator (such as phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide) has already reacted almost completely in the first step of ultraviolet curing, and no additional photocrosslinking reaction will occur during the second step of visible light irradiation, interfering with the exchange of diselenide bonds. This step-by-step control mode of curing and triggering effectively avoids the process crosstalk or substrate damage problems caused by the overlap of the triggering wavelength and curing light or the excessively high triggering temperature in traditional dynamic bond systems (such as disulfide bonds), thus providing a larger window for parameter optimization of the nanoimprinting process.
[0032] In summary, this invention combines the rigid framework effect of polymerizable ligand-modified tetrapod quantum dots with the dynamic topological rearrangement mechanism of diselenylene bonds, achieving ultra-low curing shrinkage, easy demolding, long template life, high filling rate, and high pattern fidelity while maintaining high crosslinking density and network integrity. This provides a new strategy for high-precision, high-yield electronic semiconductor nanoimprint adhesives. Detailed Implementation
[0033] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] According to a first aspect of the present invention, a nanoimprinting adhesive for electronic semiconductor manufacturing is provided, comprising the following raw materials in parts by weight: 40-60 parts of crosslinkable resin containing double bonds; 8-20 parts of polymerizable ligand-modified semiconductor quantum dots; 15-40 parts of reactive diluent; 1-5 parts of photoinitiator; 10-25 parts organic solvent.
[0035] Furthermore, polymerizable ligand-modified semiconductor quantum dots comprise: Semiconductor quantum dots, and Polymerizable ligands covalently bonded to their surface.
[0036] Furthermore, the general structural formula of polymerizable ligands is as follows: CH2=C(CH3)-C(O)-O-(CH2) n -Se-Se-(CH2) m -SH; Where n = 2 - 6, m = 2 - 6, and n and m are both integers.
[0037] Furthermore, n = 2 - 4, m = 2 - 4, where n and m are both integers.
[0038] Furthermore, the semiconductor quantum dot is a four-legged quantum dot.
[0039] Furthermore, the tetrapod quantum dot is selected from at least one of group II-VI semiconductor tetrapod quantum dots and group III-V semiconductor tetrapod quantum dots.
[0040] Furthermore, the tetrapod quantum dot is a group II-VI semiconductor tetrapod quantum dot, which includes, but is not limited to, tetrapod CdSe quantum dots.
[0041] Furthermore, the crosslinkable resin containing double bonds is selected from at least one of bisphenol A epoxy acrylate and phenolic epoxy acrylate; the reactive diluent is an acrylate reactive diluent, which includes, but is not limited to, trimethylolpropane triacrylate (TMPTA); the organic solvent is selected from at least one of alcohol ether organic solvents, ester organic solvents and ketone organic solvents; the photoinitiator is selected from at least one of acylphosphine oxide photoinitiators, α-hydroxy ketone photoinitiators, α-amino ketone photoinitiators, aromatic ketone photoinitiators and thioxanthone photoinitiators.
[0042] Furthermore, the organic solvent is an alcohol ether organic solvent, including but not limited to propylene glycol methyl ether acetate (PGMEA); the photoinitiator is an acylphosphine oxide photoinitiator, including but not limited to phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0043] According to a second aspect of the present invention, a method for preparing nanoimprint adhesive for electronic semiconductor manufacturing is provided, comprising the following steps: S1. Preparation of polymerizable ligand-modified semiconductor quantum dots; S2. Under light-protected conditions, the polymerizable ligand-modified semiconductor quantum dots from step S1 are ultrasonically dispersed in an organic solvent to form a quantum dot pre-dispersion. S3. Add crosslinkable resin containing double bonds, reactive diluent and photoinitiator sequentially to the quantum dot predispersant formed in step S2, stir and mix evenly; after vacuum degassing and filtration, obtain nanoimprint adhesive.
[0044] The application method of nano-imprint adhesive is as follows: (1) The substrate was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, dried with nitrogen and then treated with oxygen plasma at a power of 40-60W for 1-3 minutes. (2) Spin coat the nanoimprint adhesive onto the substrate at a speed of 1000-2000 r / min for 30-90 s, with a layer thickness of 150-200 nm. Then bake it on a hot plate at 80-90℃ for 90-120 s to remove the organic solvent. (3) Align the template with the micro-nano structure pattern with the substrate coated with imprinting adhesive, apply a pressure of 1-3 bar, and hold the pressure for 30-90 seconds; (4) Curing by ultraviolet light irradiation under an inert gas atmosphere; (5) Vertically lifting the template separates the template from the imprinting adhesive, thus obtaining a nanoimprint pattern; (6) Post-curing with visible light to obtain cured adhesive film material; The curing parameters are: wavelength 365nm, light intensity 40-60mW / cm². 2 Light exposure time: 10-30 seconds; The vertical lifting speed of the template is 0.1-0.2 mm / s; The post-curing parameters are: wavelength 405-450nm, light intensity 20-40mW / cm². 2 The illumination time is 30-90 seconds.
[0045] Furthermore, the method for preparing polymerizable ligand-modified semiconductor quantum dots is as follows: Oleic acid-terminated semiconductor quantum dots were dispersed in anhydrous ethanol under an inert gas atmosphere. The pH of the system was adjusted to 5.0-6.5, polymerizable ligands and antioxidants were added, and the reaction was carried out at 50°C in the dark for 12-24 hours with stirring. After precipitation with acetone, centrifugation, redispersion and purification with toluene, and vacuum drying, polymerizable ligand-modified semiconductor quantum dots were obtained.
[0046] Furthermore, the mass ratio of semiconductor quantum dots to polymerizable ligands is 100:(3-8); the amount of antioxidant added is 0.01wt.%-0.1wt.%.
[0047] Furthermore, the mass ratio of semiconductor quantum dots to polymerizable ligands is 100:5; the amount of antioxidant added is 0.01wt.%-0.05wt.%.
[0048] Furthermore, the antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol (BHT), 4,4'-butylene-bis(6-tert-butyl-3-methylphenol) (BBM), antioxidant 1726, and antioxidant 1010.
[0049] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol (BHT).
[0050] Furthermore, the parameters for ultrasonic dispersion in step S2 are as follows: ultrasonic power 100-200W, time 20-40min.
[0051] Furthermore, the parameters for uniform mixing in step S3 are as follows: rotation speed 800-1200 r / min, time 30-60 min.
[0052] Furthermore, inert gases include, but are not limited to, nitrogen.
[0053] According to a third aspect of the present invention, the application of the nanoimprint adhesive prepared by the preparation method in electronic semiconductor manufacturing is provided.
[0054] Preparation Example 1 Preparation of polymerizable ligand-modified tetrapod CdSe quantum dots 1. Synthesis of polymerizable ligands containing diselenyl bonds (1) Activation pretreatment of selenium powder Weigh 420g of selenium powder (Se) and place it in a 2L beaker. Add 1L of 1M dilute hydrochloric acid and stir at 200 rpm for 15 min at room temperature. After allowing the precipitate to stand, discard the supernatant and wash repeatedly with deionized water 5 times until the pH of the washing solution is (7.0±0.2). Transfer the washed selenium powder to a Buchner funnel for vacuum filtration, collect the filter cake, and dry it in a vacuum drying oven at 40℃ for 6 h to obtain approximately 400g of activated selenium powder.
[0055] (2) Preparation of sodium diselenide (Na2Se2) solution Add 40g NaOH and 6L degassed deionized water to a 20L reaction flask and stir at 200r / min until completely dissolved. Vacuum the reaction flask and circulate nitrogen three times to replace the air inside. Add 400g of the activated selenium powder (Se) obtained in step (1) and stir until the system is evenly dispersed. Then add 96g of sodium borohydride (NaBH4) in batches of 10g each time (6g for the last batch), with an interval of 2-3min between batches, maintaining good ventilation during operation. After the addition is complete, allow it to cool naturally to room temperature. Take the reflux condenser and fix it vertically to the top of the reaction flask. Connect the inlet of the condenser jacket to a room temperature circulating water pipe to ensure continuous cooling water flow. Connect a nitrogen bag to the outlet at the top of the condenser to maintain a slight positive pressure (the balloon is slightly inflated) throughout the reaction system to prevent backflow of air. Place the connected reaction flask in a 50°C oil bath and heat and stir for 2.5 hours. When the solution changes from black to light yellow and clear, stop heating, maintain a nitrogen atmosphere, and allow it to cool naturally to room temperature to obtain a sodium diselenide (Na2Se2) solution.
[0056] (3) Synthesis of diselenodiol intermediate Dissolve 400g of 2-bromoethanol in 4L of anhydrous tetrahydrofuran (THF), add it to a 20L reaction flask, and stir at 300r / min until completely dissolved. Place the reaction flask in an ice-water bath and stir to cool until the internal temperature is below 10℃. Transfer all the Na2Se2 solution obtained in step (2) to a constant pressure dropping funnel in three portions (2L each time), and slowly add it dropwise to the reaction flask, controlling the dropping rate at 30mL / min, and keeping the system temperature below 10℃. After the dropping is complete, remove the ice bath, allow the system to rise naturally to room temperature, and continue stirring for 12h. After the reaction is complete, the reaction solution gradually turns yellow. In a fume hood, slowly add 8L of deionized water to quench the reaction. Transfer the mixture to a 20L separatory funnel, extract with ethyl acetate (4L / time, 3 times in total), and combine the organic phases. Add 2kg of anhydrous sodium sulfate and dry for 1h, filter, wash the filter cake with 1L of ethyl acetate, and combine the filtrates. The filtrate was concentrated three times in a rotary evaporator in the dark (water bath temperature 38℃, vacuum degree 25mbar, receiving flask wrapped with aluminum foil) to obtain a deep yellow oily crude product. This crude product was purified by silica gel column chromatography (2kg silica gel, column diameter 15cm, petroleum ether:ethyl acetate = 3:1, mobile phase pre-degassed with nitrogen). The yellow fraction was collected and concentrated to obtain the intermediate diselenodiol (structural formula: HO-(CH2)2-Se-Se-(CH2)2-OH), a yellow oily substance, with a yield of approximately 193g.
[0057] Nuclear magnetic resonance selenium spectroscopy was performed on the above intermediate diselenodiol. 77 Characterization by Se NMR showed that characteristic Se-Se absorption peaks appeared in the range of 280-300 ppm, proving that the diselenide bond structure was intact.
[0058] (4) Synthesis of polymerizable ligands containing thiol-diselelenide bonds In a 5L three-necked flask, add 100g of diselenodiol, the intermediate obtained in step (3), and 2L of anhydrous dichloromethane, and stir until completely dissolved. Add 55mL of triethylamine, place the three-necked flask in an ice-water bath, and stir to cool until the internal temperature is below 10℃. Slowly add 40mL of methacryloyl chloride under a nitrogen atmosphere, controlling the dropping rate at 30mL / min, and keep the system temperature below 10℃. After the addition is complete, continue the reaction in an ice bath for 2 hours, remove the ice bath, and allow the system to naturally rise to room temperature. Continue stirring for 12 hours. Wash the reaction solution twice with 1L of saturated sodium bicarbonate solution to separate the aqueous phase. Dry the organic phase with anhydrous sodium sulfate, filter, and concentrate the filtrate on a rotary evaporator in the dark (water bath temperature 38℃, vacuum degree 25mbar, receiving flask wrapped with aluminum foil) to obtain the crude product. The crude product was purified by silica gel column chromatography (2 kg silica gel, 15 cm column diameter, petroleum ether: ethyl acetate = 5:1, mobile phase pre-degassed with nitrogen) to obtain a pale yellow oily monoester with a yield of approximately 61 g.
[0059] Dissolve 61g of the monoester product in 1L of anhydrous dichloromethane, add 40mL of triethylamine, and place in an ice-water bath. Stir and cool until the internal temperature is below 10℃. Slowly add 20mL of methanesulfonyl chloride under a nitrogen atmosphere. After the addition is complete, react in an ice-water bath for 2 hours, then allow to naturally warm to room temperature and continue the reaction for another 2 hours. After the reaction is complete, slowly add 500mL of deionized water to quench the reaction. Extract with dichloromethane (500mL / time, 3 times in total). Wash the organic phase successively with 1M HCl (200mL), saturated sodium bicarbonate solution (200mL), and saturated sodium chloride solution (200mL). Dry with anhydrous sodium sulfate, filter, and concentrate under reduced pressure to obtain crude methanesulfonate product, yielding approximately 74g.
[0060] The 74g crude methanesulfonate obtained above was dissolved in 500mL of anhydrous N,N-dimethylformamide (DMF), and 35g of potassium thioacetate was added. The mixture was stirred at room temperature for 12h under a nitrogen atmosphere. After the reaction, 1L of deionized water was added for dilution, and the mixture was extracted with dichloromethane (500mL / time, 3 times in total). The organic phase was dried over anhydrous sodium sulfate, filtered, concentrated under reduced pressure, and then mixed with 2L of 5% NaOH solution. The mixture was stirred at room temperature for 2h for hydrolysis. The organic phase was separated, and the aqueous phase was neutralized to pH (2.5±0.2) with 1M HCl and extracted with dichloromethane (500mL / time, 3 times in total). The organic phases were combined, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure in the dark to obtain the crude product. The crude product was purified by column chromatography (2kg silica gel, 15cm column diameter, petroleum ether:ethyl acetate = 4:1, mobile phase pre-degassed with nitrogen) to obtain a polymerizable ligand with a yield of approximately 60g. Its structural formula is as follows: CH2=C(CH3)-C(O)-O-(CH2)2-Se-Se-(CH2)2-SH.
[0061] The polymerizable ligands were characterized, and the results showed that: ESI-MS mass spectrometry: positive ion mode, m / z 359.1 [M+H] + It is basically consistent with the target molecular weight.
[0062] 1H NMR spectrum ( 1 H NMR) (400MHz, CDCl3): δ6.15(s, 1H, =CHH), δ5.54(s, 1H, =CHH), δ4.43(t, J=6.5Hz, 2H, OCH2), δ3.11(t, J=7.2Hz, 2H, SeCH2), δ2.72(t, J=7.0Hz, 2H, SCH2), δ1.96(s, 3H, CH3C=), δ1.44(t, J=7.8Hz, 1H, SH).
[0063] 2. Quantum dot ligand exchange 10 g of oleic acid-terminated tetrapod-shaped CdSe quantum dots (average particle size 8 nm) were dispersed in 60 mL of toluene and centrifuged at 8000 r / min for 10 min at 4 °C. The supernatant was discarded, and the precipitate was dispersed in 0.3 L of anhydrous ethanol pre-degassed with nitrogen to obtain a dispersion. 50 mL of 0.1 M citrate buffer (pH 5.0) was added to the dispersion to adjust the pH to (5.5 ± 0.2). Subsequently, 10 g of the polymerizable ligand obtained in step 1 and 60 mg of 2,6-di-tert-butyl-4-methylphenol (BHT) were added, and the mixture was transferred to a 5 L three-necked flask. A reflux condenser was installed, and the mixture was evacuated and purged with nitrogen three times. The mixture was then stirred and reacted at 50 °C in the dark for 24 h.
[0064] After the reaction was completed, the mixture was allowed to cool naturally to room temperature. 0.6 L of pre-cooled acetone (-20 °C) was added, and the mixture was centrifuged at 8000 r / min for 10 min at 4 °C. The precipitate was collected and resuspended in 0.1 L of toluene containing 0.01 wt.% BHT. The acetone precipitation, centrifugation, and toluene resuspension process was repeated twice (a total of 3 times). The last precipitate was collected and dried in a freeze dryer at -20 °C for 12 h to obtain polymerizable ligand-modified tetrapod CdSe quantum dots with a yield of approximately 19 g.
[0065] Approximately 19g of polymerizable ligand-modified tetrapod CdSe quantum dots can be prepared by using 10g of polymerizable ligand, and approximately 108g of polymerizable ligand-modified tetrapod CdSe quantum dots can be prepared in batches by using 60g of polymerizable ligand.
[0066] The tetrapod-shaped CdSe quantum dots modified with polymerizable ligands were characterized and their functionality verified. The results showed that: X-ray photoelectron spectroscopy (XPS): Characteristic peaks of Se 3d and S 2p were detected, where Se 3d... 5 / 2 The binding energy is 54.6 eV, and the S 2p binding energy is 162.5 eV, indicating that the diselenylene ligand has been successfully covalently bonded to the quantum dot surface.
[0067] FTIR spectroscopy: C=O stretching vibration peak of the original oleic acid ligand (approximately 1700 cm⁻¹) -1 The significant disappearance of the oleic acid ligand indicates that the oleic acid ligand has been effectively replaced.
[0068] Dynamic light scattering (DLS): When polymerizable ligand-modified tetrapod CdSe quantum dots were dispersed in propylene glycol methyl ether acetate (PGMEA) at a concentration of 0.5 mg / mL, the Z-average particle size changed within ±15% relative to the oleic acid-terminated quantum dots before ligand exchange, and the polydispersity index (PDI) was <0.2, indicating that the quantum dots were stably dispersed in the solvent and did not agglomerate.
[0069] Functional Validation: 5 mg of polymerizable ligand-modified tetrapod CdSe quantum dots were dispersed in 1 mL of methyl methacrylate (MMA), and 0.5 mg of AIBN was added. Polymerization was carried out at 65 °C for 4 h under nitrogen protection, yielding a yellow transparent solid. In a control experiment, oleic acid-terminated tetrapod CdSe quantum dots were used instead of polymerizable ligand-modified tetrapod CdSe quantum dots; under the same conditions, obvious black agglomerated particles appeared in the polymerized solid. This result indicates that the polymerizable ligands on the surface of the polymerizable ligand-modified tetrapod CdSe quantum dots successfully participated in the free radical copolymerization of MMA, and the double bond function remained intact.
[0070] Preparation Example 2 Tetrapod CdSe quantum dots modified with methacrylate ligands 20g of oleic acid-terminated tetrapod-shaped CdSe quantum dots (average particle size 8nm) were dispersed in 2L of anhydrous ethanol, and 10g of mercapto-polyethylene glycol methacrylate (Mn≈1000, purchased from Shanghai Tuoyang Biotechnology Co., Ltd.) was added. The mixture was then transferred to a 5L three-necked flask. A reflux condenser was installed, and the mixture was evacuated and purged with nitrogen three times. The mixture was then stirred and reacted for 12h under nitrogen atmosphere, 50℃, and in the dark.
[0071] After the reaction was completed, 3L of pre-cooled acetone (-20℃) was added to precipitate the tetrapod CdSe quantum dots. The precipitate was centrifuged at 8000r / min at 4℃ for 10min (5 centrifugations, 1L / centrifugation). The precipitate was collected and resuspended in 0.5L of toluene containing 0.01wt.% BHT. The precipitate was precipitated again with acetone, centrifuged, and resuspended in toluene. This process was repeated twice (3 times in total). The last precipitate was collected and dried at -20℃ for 12h using a freeze dryer to obtain methacrylate ligand-modified tetrapod CdSe quantum dots with a yield of approximately 20g.
[0072] Example 1 A nanoimprint stencil for use in electronic semiconductor manufacturing, comprising the following raw materials: Bisphenol A epoxy acrylate 45g; 15g of polymerizable ligand-modifiable tetrapod-shaped CdSe quantum dots; 22g of trimethylolpropane triacrylate; 3g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; 15g of propylene glycol methyl ether acetate.
[0073] The preparation method of nanoimprint adhesive includes the following steps: S1. Under light-protected conditions, the polymerizable ligand-modified tetrapod CdSe quantum dots prepared in the preparation example were added to propylene glycol methyl ether acetate and ultrasonically dispersed at 150 W for 30 min to form a quantum dot pre-dispersion. S2. Under light-protected conditions, bisphenol A epoxy acrylate, trimethylolpropane triacrylate, and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide were added sequentially to the quantum dot pre-dispersion solution formed in step S1. The mixture was stirred at 1000 r / min for 45 min until homogeneous. Vacuum degassing was then performed at -0.08 MPa for 15 min until no visible bubbles were observed. Finally, the mixture was pressure filtered through a 0.45 μm polytetrafluoroethylene (PTFE) membrane, and the filtrate was collected to obtain the nanoimprint adhesive.
[0074] The application method of nanoimprint adhesive includes the following steps: (1) The 8-inch silicon substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 min in sequence, dried with nitrogen and then treated with oxygen plasma for 2 min (power 50W, oxygen flow rate 50sccm). (2) The nanoimprint adhesive prepared above was spin-coated onto the silicon substrate at a speed of 1500 r / min (spin-coating time 60s), and the adhesive layer thickness was about (180±5) nm. Then it was baked on a hot plate at 90℃ for 90s to remove the organic solvent. (3) Align the quartz template with micro-nano structure pattern (line width 50nm, aspect ratio 3:1) with the silicon substrate coated with imprinting adhesive, apply 2 bar pressure and hold for 60s; (4) Under a nitrogen atmosphere, use a 365nm ultraviolet lamp at 50mW / cm 2 Curing was performed by irradiation with light intensity for 20 seconds, and the double bond conversion rate was >90% as measured by Fourier transform infrared spectroscopy (FTIR). (5) Vertically lift the template at a speed of 0.2 mm / s to separate the template from the imprinting adhesive and obtain a nanoimprint pattern; (6) Using a 405nm LED light source at 30mW / cm 2 The material is post-cured by irradiation with light intensity for 60 seconds to obtain the cured adhesive film material.
[0075] Example 2 The difference between Example 2 and Example 1 is that Example 2 is a nanoimprint adhesive for electronic semiconductor manufacturing, comprising the following raw materials: Bisphenol A epoxy acrylate 40g; 8g of polymerizable ligand-modified tetrapod-shaped CdSe quantum dots; 40g of trimethylolpropane triacrylate; 2g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; 10g of propylene glycol methyl ether acetate.
[0076] The preparation method and usage method are the same as in Example 1.
[0077] Example 3 The difference between Example 3 and Example 1 is that Example 3 is a nanoimprint adhesive for electronic semiconductor manufacturing, comprising the following raw materials: Bisphenol A epoxy acrylate 60g; 14g of polymerizable ligand-modified tetrapod-shaped CdSe quantum dots; 15g of trimethylolpropane triacrylate; 1 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide; 10g of propylene glycol methyl ether acetate.
[0078] The preparation method and usage method are the same as in Example 1.
[0079] Example 4 The difference between Example 4 and Example 1 is that Example 4 is a nanoimprinting adhesive for electronic semiconductor manufacturing, comprising the following raw materials: Bisphenol A epoxy acrylate 40g; 10g of polymerizable ligand-modified tetrapod-shaped CdSe quantum dots; 20g of trimethylolpropane triacrylate; 5g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; Propylene glycol methyl ether acetate 25g.
[0080] The preparation method and usage method are the same as in Example 1.
[0081] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 lacks the tetrapod CdSe quantum dots that can be modified with polymerizable ligands.
[0082] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the tetrapod CdSe quantum dots modified with methacrylate ligands obtained in Preparation Example 2 are used instead of the tetrapod CdSe quantum dots modified with polymerizable ligands.
[0083] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that nano-SiO2 is used instead of polymerizable ligand-modified tetrapod CdSe quantum dots.
[0084] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that step (5) is missing in the method of use, that is, the mold is directly removed after imprinting without visible light irradiation.
[0085] Test Example 1 Colloidal basic properties and curing shrinkage test To evaluate the basic properties of the nanoimprint adhesive of the present invention, the viscosity of the nanoimprint adhesive before curing in Examples 1-4 and Comparative Examples 1-4, and the curing shrinkage rate of the adhesive film materials after curing in Examples 1-4 and Comparative Examples 1-4 were tested. The specific test methods are as follows: (1) Viscosity test: The test was conducted according to GB / T 22235-2008 "Determination of Viscosity of Liquids". Before testing, the nanoimprint adhesive was equilibrated in a 25℃ constant temperature water bath for 30 minutes. A Brookfield DV2T rotational viscometer (rotor model S18, suitable for low-viscosity fluids) was used. The rotor was slowly immersed in the adhesive up to the marked line on the rotor rod, ensuring the rotor was fully wetted. Rotation speeds were set to 10 r / min and 100 r / min, and viscosity values were recorded after the torque stabilized (usually 30-60 s). Three consecutive readings were taken at each rotation speed, and the arithmetic mean was recorded. After each measurement, the pointer was allowed to return to zero before the next measurement was performed. Eight parallel samples were prepared for each sample.
[0086] Evaluation criteria: The dynamic viscosity measured at 25℃ and 10r / min is 5-30mPa·s.
[0087] (2) Curing shrinkage rate test: The test was conducted according to GB / T 1033.1-2008 "Determination of density of non-foamed plastics - Part 1: Impregnation method, liquid pyrometer method and titration method". Uncured nanoimprint adhesive from each experimental group was carefully injected into a clean, dry 50mL pyrometer bottle to full volume. The bottle was then capped to eliminate air bubbles and placed in a 25℃ constant temperature water bath for 30 minutes to equilibrate. After absorbing excess adhesive with filter paper, the contents were weighed. m 2), and weighed using an empty specific gravity bottle ( m 1) Calculate the liquid density using the following formula. r 1: ; Note: m 1 represents the mass (g) of the empty specific gravity bottle; m 2 indicates the mass (g) of the specific gravity bottle after it is filled with uncured adhesive; V This indicates the volume of the specific gravity bottle (50 mL).
[0088] Take the cured adhesive film material from each experimental group, scrape off (0.8±0.2) g of adhesive film powder with a scalpel, and determine the density of the adhesive film according to the liquid specific gravity bottle method described above. r 2. Prepare 8 parallel samples for each sample and take the arithmetic mean.
[0089] Calculate the post-curing shrinkage rate (Δ, %) using the following formula: ; Note: r 1 indicates the density of the liquid before curing; r 2 indicates the density of the cured adhesive film.
[0090] Evaluation criteria: Volume shrinkage rate after curing <2.5%.
[0091] The results are shown in Table 1 below: Table 1. Test results of viscosity and curing shrinkage rate of nanoimprint adhesive under different formulations and processes (n=8)
[0092] Note: Compared with Examples 1-4, the viscosity of the nanoimprint adhesive in Comparative Examples 1-3 differed significantly. p <0.05); Compared with Examples 1-4, the curing shrinkage rates of the adhesive film materials in Comparative Example 1 and Comparative Example 2 differed significantly ( p <0.05), the curing shrinkage rate of the adhesive film materials in the three comparative groups did not differ significantly ( p >0.05). In the comparative example group 4, template contamination and graphic defects occurred during the actual imprinting process, while the templates of the other experimental groups were free of contamination and graphic defects.
[0093] It can be seen from Table 1 above: In Examples 1-4, the viscosity of the nanoimprint adhesive was within the range of 11.1-15.6 mPa·s, all meeting the judgment criteria. In Comparative Example 1, which lacked polymerizable ligand-modified tetrapod CdSe quantum dots, and Comparative Example 2, which used methacrylate-modified tetrapod CdSe quantum dots instead of polymerizable ligand-modified tetrapod CdSe quantum dots, the viscosities of the nanoimprint adhesive were (25.0±2.6) mPa·s and (27.0±2.4) mPa·s, respectively, both meeting the judgment criteria, but significantly higher than those in Examples 1-4. p The viscosity of the nanoimprint adhesive was <0.05 mPa·s. This may be because the resin itself has a high viscosity when polymerizable ligand-modified tetrapod CdSe quantum dots are missing; while methacrylate ligand-modified quantum dots have poor compatibility with the resin and are prone to aggregation, leading to increased flow resistance. In the comparative example group 3, where nano-SiO2 was used to replace polymerizable ligand-modified tetrapod CdSe quantum dots, the viscosity of the nanoimprint adhesive was (35.6±2.5) mPa·s, which did not meet the judgment criteria. This may be because ordinary inorganic nanofillers (such as nano-SiO2) lack organic modification on their surface, have poor compatibility with the resin, and are prone to aggregation, forming physical barriers that hinder molecular chain flow, resulting in a significant increase in system viscosity and failing to meet the low viscosity requirements of the nanoimprint process. Therefore, polymerizable ligand-modified quantum dots are the key component for controlling the viscosity of nanoimprint adhesives.
[0094] In Examples 1-4, the curing shrinkage rate of the cured adhesive film materials was within the range of 1.5%-2.0%, all meeting the judgment criteria. In Comparative Example 3, where nano-SiO2 replaced polymerizable ligand-modified tetrapod CdSe quantum dots, the curing shrinkage rate of the cured adhesive film materials was (2.1±0.2)%, lower than that of Examples 1-4. pThe shrinkage rate was >0.05%, which may be due to the lack of polymerizable groups on the surface of nano-SiO2, making it impossible to inhibit resin shrinkage through chemical bonding. Furthermore, the low addition amount had limited effect on improving the shrinkage rate. In Comparative Example 1, which lacked polymerizable ligand-modified tetrapod CdSe quantum dots, and Comparative Example 2, which used methacrylate-modified tetrapod CdSe quantum dots instead of polymerizable ligand-modified tetrapod CdSe quantum dots, the curing shrinkage rates of the cured film materials were (3.1±0.4)% and (2.7±0.2)%, respectively, both failing to meet the judgment criteria. This may be because the absence of polymerizable ligand-modified tetrapod CdSe quantum dots completely lost its anchor point for inhibiting shrinkage; while the use of methacrylate-modified tetrapod CdSe quantum dots resulted in significantly lower polymerization activity and double bond conversion rate compared to acrylate ligands due to the steric hindrance of the α-methyl group in the methacrylate ligand, making it difficult to effectively participate in the crosslinking network. Neither method effectively inhibited polymerization shrinkage, leading to excessive curing shrinkage. This demonstrates that polymerizable ligand-modified quantum dots are key components that inhibit curing shrinkage by participating in cross-linking networks.
[0095] It is worth noting that in the four comparative examples without visible light irradiation, the viscosity of the nanoimprint adhesive was (17.5±2.2) mPa·s, and the curing shrinkage rate of the cured film material was (1.4±0.2)%. Although both met the judgment criteria, template contamination and pattern defects occurred in the actual imprinting process. This may be due to the lack of a visible light post-curing step. Although the basic indicators such as viscosity and shrinkage rate were qualified after UV primary curing, the cross-linking network of the film was incomplete, with a large amount of unreacted oligomers and free radicals remaining. During demolding, these oligomers migrated to the template surface to form a contamination layer, and the insufficient cohesive strength of the film led to pattern defects. Therefore, qualified basic performance indicators do not represent the overall process reliability; the integrity of the network formed after complete curing must be evaluated.
[0096] Test Example 2 Demolding force and template life test To evaluate the release performance and template compatibility of the nano-imprint adhesive of this invention, the release force and template life of the cured adhesive film materials in Examples 1-4 and Comparative Examples 1-4 were tested. The specific test methods are as follows: (1) Demolding force test: A high-precision force gauge (Mark-10 series, range 0-500N) is integrated into the demolding shaft of the UV nanoimprint equipment, with the center line of the force sensor aligned with the center of the template. After imprinting and curing, the template is vertically lifted at a constant speed of 0.5mm / s, with a lifting displacement of 10-20mm, and the data acquisition frequency is no less than 100Hz. The force-displacement curve during demolding is recorded, and the peak demolding force (i.e., the maximum value of the curve) is read. Each sample is subjected to the imprinting-demolding cycle 10 times, and the arithmetic mean is taken as the demolding force value of that sample.
[0097] Evaluation criteria: Peak demolding force ≤ 30N.
[0098] (2) Template life test: A fully automated ultraviolet nanoimprint transfer device was used to repeatedly perform imprint-demolding cycles on the same template. After a certain number of cycles, the demolding force of the current cycle was measured according to the demolding force testing method described above, and the demolding force rise rate was calculated using the following formula. : ; After every 50 cycles, the water contact angle on the template surface is measured using a contact angle meter to evaluate the degree of anti-adhesion layer wear; simultaneously, an optical microscope is used to inspect the template surface for resin residue, anti-adhesion layer peeling, or pattern damage. The template life is taken as the smaller of the following two values: (a) The number of cycles prior to when the rate of increase in demolding force first reaches or exceeds 50%; (b) The number of cycles prior to the occurrence of obvious graphic defects (such as missing graphics, deformation, resin residue, etc.).
[0099] Evaluation criteria: Maximum effective number of cycles ≥ 500 times (i.e. the template can be reused at least 500 times without the demolding force increase rate ≥ 50% or obvious graphic defects).
[0100] The results are shown in Table 2 below: Table 2. Test results of demolding force and template life of cured adhesive film materials under different formulations and processes (n=8)
[0101] Note: Compared with Examples 1-4, the release force of the cured adhesive film material in Comparative Examples 1-3 was significantly different. p <0.05); Compared with Examples 1-4, the template life of the cured adhesive film material in Comparative Example 1 and Comparative Example 3 was significantly different ( p <0.05), the template life of the adhesive film materials in the two comparative groups was not significantly different ( p >0.05). In the comparative example group 4, template contamination and graphic defects occurred during the actual imprinting process, while the templates of the other experimental groups were free of contamination and graphic defects.
[0102] It can be seen from Table 2 above: The release force of the cured adhesive film materials in Examples 1-4 was within the range of 12.8-20.4 N, all meeting the judgment criteria. The release force of the cured adhesive film materials in Comparative Example 2, where tetrapod-shaped CdSe quantum dots modified with methacrylate ligands were used instead of polymerizable ligand-modified tetrapod-shaped CdSe quantum dots, was (23.8±2.7) N. Although this met the judgment criteria, it was significantly higher than that of Examples 1-4. p <0.05). This may be because the methacrylate ligands do not contain diselenyl bonds, and therefore cannot undergo a reversible exchange reaction under visible light irradiation, resulting in a lack of topological rearrangement ability in the cured crosslinked network. The internal stress accumulated during the imprinting and curing process cannot be effectively released, increasing the adhesion between the film and the template, thus significantly increasing the release force. In Comparative Example 1, which lacks polymerizable ligand-modified tetrapod CdSe quantum dots, and Comparative Example 3, which uses nano-SiO2 to replace polymerizable ligand-modified tetrapod CdSe quantum dots, the release forces of the cured film materials were (30.7±2.6) N and (36.4±2.2) N, respectively, both failing to meet the judgment criteria. This may be because the modulus is too high and there is a lack of stress release mechanism when polymerizable ligand-modified tetrapod CdSe quantum dots are missing; while the use of ordinary inorganic nanofillers (such as nano-SiO2) causes uneven modulus, uncontrolled adhesion, and template scratching due to agglomeration. Both cause the release force to exceed the standard. Therefore, polymerizable ligand-modified quantum dots are an indispensable component for achieving effective control of release force.
[0103] In Examples 1-4, the template life of the cured adhesive film materials was in the range of 601-1137 cycles, all meeting the judgment criteria. In Comparative Example 1 (lacking polymerizable ligand-modified tetrapod CdSe quantum dots), Comparative Example 2 (using methacrylate-modified tetrapod CdSe quantum dots instead of polymerizable ligand-modified tetrapod CdSe quantum dots), and Comparative Example 3 (using nano-SiO2 instead of polymerizable ligand-modified tetrapod CdSe quantum dots), the template life of the cured adhesive film materials was in the range of 183-485 cycles, none meeting the judgment criteria. This is likely because the polymerizable ligand-modified tetrapod CdSe quantum dots participate in crosslinking, forming a strong and tough network that concentrates release stress at the interface, achieving clean peeling. Conversely, the absence of these polymerizable ligand-modified tetrapod CdSe quantum dots, or the use of ligands with poor polymerizability (such as methacrylate), leads to crosslinking defects, insufficient cohesive strength, and a tendency for cohesive failure and residual adhesive film. Using ordinary inorganic nanofillers (such as nano-SiO2) results in stress concentration and uncontrolled adhesion due to a lack of reactive groups and a tendency to aggregate. All three methods fail to achieve the required template lifetime. Therefore, polymerizable ligand-modified tetrapod CdSe quantum dots are crucial for achieving a long template lifetime.
[0104] It is worth noting that in the four comparative examples without visible light irradiation, the release force of the cured film material was (11.1±2.5) N, which met the judgment criteria, but its template life was the lowest, only (183±68) cycles. Furthermore, template contamination and defects in the patterned areas occurred during the actual imprinting process. This may be due to the lack of a visible light post-curing step, resulting in incomplete cross-linking of the film. While low cross-linking reduces the release force, a large amount of unreacted oligomers and residual free radicals contaminate the template during demolding, and insufficient cohesive strength easily leads to cohesive breakage, resulting in film residue and accelerating template failure. Therefore, a low release force value does not necessarily indicate superior overall performance; the integrity of the fully cross-linked network must be ensured.
[0105] Test Example 3 Stress relaxation and network integrity testing To evaluate the internal stress release capability and cured network integrity of the nanoimprint adhesive of the present invention, the stress relaxation characteristics and gel content of the cured adhesive film materials in Examples 1-4 and Comparative Examples 1-4 were tested. The specific test methods are as follows: (1) Stress relaxation test: A TA Q800 dynamic thermomechanical analyzer, equipped with tensile fixtures and a 405nm LED light source (adjustable intensity), was used. The cured adhesive film material from each experimental group was cut into rectangular specimens with a length of (20±0.5) mm, a width of (5±0.2) mm, and a thickness of (0.8±0.2) mm, ensuring the specimens were flat and free of visible defects. The specimens were mounted on DMA tensile fixtures with a fixture spacing of (10±0.1) mm and a preload of 0.01 N was applied. A tensile strain of 1% was applied at a constant rate at a constant temperature of 25℃, and this strain value was kept constant. The stress-time curve (stress relaxation curve) was recorded, and the test time was 120 min. Exponential decay fitting was performed on each stress relaxation curve to extract the characteristic relaxation time. t ½ (min) is defined as the time required for the stress to decay to half of the initial stress. Three parallel specimens were prepared for each sample, and the arithmetic mean was taken. t ½ The average value is taken as the stress relaxation characteristic time of the sample. The stress retention rate at each time point is calculated using the following formula ( s (t) ,%) : ; Note: s 0 indicates when t Initial stress (N) when =0; s t This represents the stress (N) at time t.
[0106] Evaluation criteria: t ½ ≤5min.
[0107] (2) Gel content test: Take the cured adhesive film material obtained by UV curing only, and the cured adhesive film material obtained by UV curing and visible light curing, from each experimental group. Use a scalpel to scrape off (1±0.2) g of adhesive film powder from each, and accurately weigh and record the weights as follows: w uv (UV-cured samples only) and w uv+Vis (Sample cured by UV and visible light), accurate to 0.0001g. Wrap the sample tightly with a 200-mesh stainless steel filter to ensure no powder leakage. Place the wrapped sample in a Soxhlet extractor, using acetone as the extraction solvent. Extract by reflux in an 80°C water bath for 24 hours, with the reflux rate controlled at 5 siphon cycles per hour (approximately 12 minutes / cycle). After extraction, remove the residue and dry it in a vacuum drying oven at 80°C for 5 hours until constant weight. Record the weight as follows. w ' uv (UV-cured samples only) and w ' uv+Vis (Sample cured by UV curing and visible light curing).
[0108] Calculate the absolute value (%) of the change rate of gel content under the two processes using the following formula. : ; Note: w uv The value represents the mass (g) of the UV-cured sample before extraction. w ' uv The value represents the mass (g) of the residue after extraction of the UV-cured sample only. w uv+Vis This indicates the sample mass (g) before extraction after UV curing and visible light curing. w uv+Vis The value represents the mass (g) of residue after extraction of the sample cured by ultraviolet light and visible light.
[0109] Eight parallel samples were prepared for each sample, and the arithmetic mean was taken.
[0110] Evaluation criteria: The absolute value of the change rate of gel content under both processes is ≤2%.
[0111] The results are shown in Table 3 below: Table 3. Stress relaxation characteristic time of cured adhesive film materials under different formulations and processes ( t ½ Results of tests on the absolute value of the change rate of gel content (n=8)
[0112] Note: Compared with Examples 1-4, the stress relaxation characteristic time of the cured adhesive film material in Comparative Examples 1-3 is ( t ½ The absolute values of the change rate of gel content under different processes were significantly different. p <0.05). In the comparative example group 4, template contamination and graphic defects occurred during the actual imprinting process, while the templates of the other experimental groups were free of contamination and graphic defects.
[0113] It can be seen from Table 3 above: The characteristic relaxation time of the cured adhesive film material in Examples 1-4 ( t ½ The characteristic relaxation time of the cured film materials in the two comparative groups (using methacrylate-modified tetrapod CdSe quantum dots instead of polymerizable ligand-modified tetrapod CdSe quantum dots) was within the range of 2.4-3.5 min, meeting the judgment criteria. t ½ The mean value was (4.1 ± 0.2) min, which met the evaluation criteria, but was still significantly higher than that of groups 1-4 in Examples ( ). p <0.05), which may be because the methacrylate ligands do not contain diselenyl bonds and cannot undergo reversible exchange reactions under visible light, resulting in a lack of dynamic rearrangement ability in the crosslinked network and slow stress relaxation. The characteristic relaxation time of the cured film materials in Comparative Example 1 (lacking polymerizable ligand-modified tetrapod CdSe quantum dots) and Comparative Example 3 (using nano-SiO2 instead of polymerizable ligand-modified tetrapod CdSe quantum dots) is compared. t ½ The timeframes were (5.5±0.3) min and (6.1±0.4) min, respectively, neither of which met the judgment criteria. This may be because the absence of polymerizable ligand-modified tetrapod CdSe quantum dots resulted in a film composed of highly cross-linked resin, restricting molecular chain movement and hindering stress release; while nano-SiO2, due to aggregation, formed physical cross-linking points and stress concentration zones, further impeding chain relaxation. Both factors contributed to... t ½ Significantly prolonged. This demonstrates that polymerizable ligand-modified tetrapod-shaped CdSe quantum dots are crucial for constructing moderately cross-linked, rapidly stress-relaxed networks.
[0114] In Examples 1-4, the gel content change rate of the cured film material was within the range of 0.7%-1.2%, all meeting the judgment criteria. In Comparative Example 3, where nano-SiO2 replaced polymerizable ligand-modified tetrapod CdSe quantum dots, the gel content change rate of the cured film material was (1.8±0.2)%, which met the evaluation criteria, but the absolute value of its cured gel content was still significantly higher than that of Examples 1-4. p<0.05%, which may be due to residual monomers adsorbed on the surface of nano-SiO2, leading to a slight increase in gel content. In Comparative Example 1, which lacked polymerizable ligand-modified tetrapod CdSe quantum dots, and Comparative Example 2, which replaced polymerizable ligand-modified tetrapod CdSe quantum dots with methacrylate ligand-modified tetrapod CdSe quantum dots, the gel content change rates of the cured film materials were (2.9±0.2)% and (2.6±0.2)%, respectively, neither meeting the judgment criteria. This may be because, when polymerizable ligand-modified tetrapod CdSe quantum dots are missing, the network lacks nano-anchors, and a large amount of uncrosslinked oligomers are extracted by the solvent; while the methacrylate ligand has low polymerization activity and insufficient double bond conversion, preventing the quantum dots from effectively bonding to the network, resulting in a large number of suspended chains and free components. Both of these factors contribute to the excessive gel content change rate. Therefore, polymerizable ligand-modified tetrapod CdSe quantum dots, through their efficient participation in crosslinking via surface double bonds, are key to forming a complete network and reducing the gel content change rate.
[0115] It is worth noting that the characteristic relaxation time of the cured adhesive film material in the four comparative groups that did not undergo visible light irradiation ( t ½ The time to demolding was (1.8±0.2) min, and the gel content change rate was (0.6±0.1)%, both meeting the judgment criteria. However, in actual imprinting processes, template contamination and graphic defects occurred. This may be due to the lack of a visible light irradiation curing step, resulting in incomplete curing of the film, incomplete cross-linking network, and the presence of unreacted oligomers and other soluble residues in the system. During the gel content test, acetone solvent completely dissolved these soluble components, leaving only the cross-linked network, thus the measured gel content change rate still appeared acceptable. However, during actual demolding, these unreacted oligomers migrated to the template surface, causing contamination, and insufficient cohesive strength led to film breakage, forming graphic defects. Therefore, the gel content change rate can only reflect the soluble portion of the cross-linked network and cannot simulate real demolding conditions, so it cannot be used alone to evaluate demolding reliability.
[0116] Test Example 4 Graphical accuracy and defect testing To evaluate the pattern reproduction accuracy and imprinting quality of the nanoimprinting adhesive of the present invention, the line width error, line edge roughness, and surface defect density of the nanoimprinted patterns in Examples 1-4 and Comparative Examples 1-4 were tested. The specific test methods are as follows: (1) Graphic line width error test: A Bruker Dimension Icon atomic force microscope (AFM) was used in tapping mode to minimize damage to the nanoimprint surface. Parameters were set as follows: scan range 5 μm × 5 μm, resolution 512 × 512 pixels, scan rate 0.5–1.0 Hz. Five to ten lines with distinct features and uniform spacing (designed linewidth 50 nm, 50 nm / 50 nm period) were selected from the nanoimprint patterns of each experimental group. The profile was extracted using AFM software, and the linewidth was measured at half the height of the trench (i.e., half the height of the line sidewall). Eight measurement points were taken on each of the left and right edges of each pattern line, for a total of three measurements. The arithmetic mean was used as the representative linewidth. Scan lines were cut along the edge direction (length direction), and the edge coordinates were extracted and statistically analyzed. Line edge roughness (LER) was expressed as the root mean square deviation (RMS) of the edge coordinates. Eight test points were selected in the center and edge regions of the 8-inch wafer, and each point was scanned three times, with the arithmetic mean being used. The final report includes the average value of each point and the overall 3σ deviation.
[0117] Evaluation criteria: |Linewidth error| ≤ 5nm (relative to a 50nm design linewidth), line edge roughness (LER, RMS) ≤ 3nm.
[0118] (2) Defect testing: Take the cured adhesive film material (8-inch wafer) from each experimental group and place it directly into the detection system without additional processing. Before detection, perform background calibration using a bare silicon reference wafer; the background count should be ≤10 particles / wafer (particle size ≥0.3μm). Use a KLA Tencor Surfscan SP5 laser particle counter for automatic full-wafer helical scanning. Start the SP5 for automatic full-wafer helical scanning, setting the particle size detection threshold to ≥0.3μm, with a 3mm edge subtraction. After scanning, the instrument automatically outputs the total number of particles with a diameter ≥0.3μm across the entire wafer. Calculate the particle density using the following formula: ; Note: Effective area (cm²) 2 = Total wafer area - Edge area deducted Simultaneously, an automated optical inspection (AOI) system scans the entire wafer surface, recording the total number of defects. For defects larger than 0.5 μm detected by AOI, manual re-inspection is performed using an optical microscope, and the defects are classified and recorded according to type (particles, scratches, voids, residues, etc.). If periodic recurring defects are found in the pattern area (such as pattern defects that repeatedly appear in a specific location), the template must be sent for inspection to eliminate interference from defects in the template itself.
[0119] Eight parallel samples were prepared for each sample, and the arithmetic mean was taken.
[0120] Evaluation criteria: Particle density (≥0.3μm) ≤5 particles / cm³ 2 Furthermore, during AOI re-inspection, unacceptable high-density repeatability defects caused by the colloid itself (such as bubbles, uneven cross-linking, and residues) should not be found.
[0121] The results are shown in Table 4 below: Table 4. Test results of linewidth error, line edge roughness, and surface defect density of nanoimprinted patterns under different formulations and processes (n=8)
[0122] Note: Compared with Examples 1-4, the edge roughness and surface defect density of the nanoimprinted patterns in Comparative Examples 1-3 were significantly different. p <0.05). In the comparative example group 4, template contamination and graphic defects occurred during the actual imprinting process, while the templates of the other experimental groups were free of contamination and graphic defects.
[0123] It can be seen from Table 4 above: In Examples 1-4, the linewidth error of the nanoimprinted patterns was within the range of -3.5 to 4.4 nm, all meeting the judgment criteria. In Comparative Example 1 (lacking polymerizable ligand-modified tetrapod CdSe quantum dots), Comparative Example 2 (using methacrylate-modified tetrapod CdSe quantum dots instead of polymerizable ligand-modified tetrapod CdSe quantum dots), and Comparative Example 3 (using nano-SiO2 instead of polymerizable ligand-modified tetrapod CdSe quantum dots), the linewidth error of the nanoimprinted patterns was within the range of -9.2 to 6.4 nm, all failing to meet the judgment criteria. This may be because the absence of polymerizable ligand-modified tetrapod CdSe quantum dots results in high curing shrinkage and internal stress in the adhesive film, leading to significant distortion of the pattern. Using ligands with poor polymerizability (such as methacrylate) prevents the tetrapod CdSe quantum dots from effectively bonding, causing localized deformation due to network defects. Furthermore, using ordinary inorganic nanofillers (such as nano-SiO2) results in aggregates acting as physical barriers, directly disrupting the regularity of the line edges. All three factors contribute to excessive linewidth error. Therefore, polymerizable ligand-modified quantum dots are a key component in reducing linewidth error.
[0124] In Examples 1-4, the LER RMS of the nanoimprinted patterns were in the range of 0.9-1.3 nm, all meeting the judgment criteria. In Comparative Example 2, where methacrylate-modified tetrapod CdSe quantum dots were used instead of polymerizable ligand-modified tetrapod CdSe quantum dots, and in Comparative Example 3, where nano-SiO2 was used instead of polymerizable ligand-modified tetrapod CdSe quantum dots, the LER RMS of the nanoimprinted patterns were (2.1±0.2) nm and (2.5±0.2) nm, respectively. Although both met the judgment criteria, they were significantly higher than those in Examples 1-4. p<0.05). This may be due to the low polymerization activity of methacrylate ligands, which prevents the tetrapod CdSe quantum dots from uniformly bonding to the crosslinking network, resulting in uneven local crosslinking density and edge fluctuations during curing shrinkage. Furthermore, the agglomeration of nano-SiO2 into micron-sized particles causes unevenness on the film surface, leading to increased line edge roughness. In Comparative Example 1, which lacks polymerizable ligand-modified tetrapod CdSe quantum dots, the LER RMS of the nanoimprint pattern was (3.4±0.2) nm, failing to meet the judgment criteria. This may be because the absence of polymerizable ligand-modified tetrapod CdSe quantum dots leads to an uneven crosslinking network, causing edge fluctuations due to shrinkage stress. Therefore, polymerizable ligand-modified tetrapod CdSe quantum dots are key to reducing line edge roughness.
[0125] In Examples 1-4, the particle density (≥0.3μm) of the nanoimprinted patterns ranged from 0.6 to 2.2 particles / cm². 2 Both met the judgment criteria. In Comparative Example 1, which lacked polymerizable ligand-modified tetrapod CdSe quantum dots, and in Comparative Example 2, which replaced polymerizable ligand-modified tetrapod CdSe quantum dots with methacrylate-modified tetrapod CdSe quantum dots, the particle density (≥0.3 μm) of the nanoimprinted patterns was (4.7 ± 0.3) particles / cm³, respectively. 2 and (3.1±0.4) particles / cm 2 Although all met the judgment criteria, they were still significantly higher than those of Examples 1-4 ( p <0.05). This may be due to the lack of polymerizable ligand-modified tetrapod CdSe quantum dots, resulting in incomplete curing of the pure resin system and the formation of tiny particles; while methacrylate ligand-modified quantum dots have poor compatibility with the resin, leading to partial aggregation and the formation of particles ≥0.3μm in size, thus increasing the particle density. In Comparative Example 3, where nano-SiO2 was used instead of polymerizable ligand-modified tetrapod CdSe quantum dots, the particle density (≥0.3μm) of the nanoimprinted patterns was (6.3±0.3) particles / cm³. 2 The criteria for judgment were not met. This may be due to the lack of organic modification on the surface of nano-SiO2, resulting in poor dispersibility in the resin and the formation of micron-sized aggregates that remain on or inside the film and are detected by the laser particle counter. Therefore, it is evident that polymerizable ligand-modified tetrapod-shaped CdSe quantum dots are an indispensable component for achieving low surface particle density.
[0126] It is worth noting that in the four comparative examples without visible light irradiation, the linewidth error of the nanoimprinted patterns was within the range of -3.5 to 3.0 nm, the LER RMS was (1.2 ± 0.2) nm, and the particle density (≥ 0.3 μm) was (1.5 ± 0.3) particles / cm³. 2Although all the criteria were met, template contamination and graphic defects occurred during the actual imprinting process. This may be due to the lack of a visible light post-curing step, incomplete cross-linking of the adhesive film, migration and contamination of the template by residual free radicals and oligomers during demolding, and insufficient cohesive strength leading to cohesive failure and graphic defects. Therefore, meeting the above criteria is insufficient to guarantee defect-free imprinting; the integrity of the network formed by complete curing must also be considered.
[0127] Test Example 5 High aspect ratio hole fill rate test To evaluate the filling ability of the nanoimprint adhesive of the present invention in high aspect ratio micro / nano structures, the average filling rate of the cured adhesive film materials in Examples 1-4 and Comparative Examples 1-4 was tested. The specific test methods are as follows: A quartz template with an aspect ratio of 3:1 and a linewidth of 50 nm (50 nm aperture diameter, 150 nm depth) was used. On the wafers after imprinting and curing in each experimental group, areas with uniform patterns and no obvious macroscopic defects were selected as test areas. A focused ion beam (FIB) was used to cut a cross-section in the central region of the aperture array. The cutting depth was approximately 500 nm to ensure complete exposure of the aperture bottom morphology. A low ion beam current of 80 pA was used for final polishing during cutting to reduce interference from the amorphous layer on image interpretation. Scanning electron microscopy (SEM) was used to capture cross-sectional images after FIB cutting at a magnification ≥100,000× to ensure clear differentiation of the aperture bottom boundaries. The following two parameters were measured in the cross-sectional images: h Total hole depth (original template design depth, 150nm); d The actual height to which the UV-cured adhesive fills the hole (vertical distance from the top of the hole opening to the bottom of the fill).
[0128] Calculate the fill rate (%) of a single hole using the following formula. : ; Note: d Indicates the actual depth of film filling (nm); h This indicates the total design depth of the hole (150nm).
[0129] Four holes were selected from the center and four from the edge of each wafer, for a total of eight holes, for measurement (the number can be reduced appropriately if the central area has better uniformity, but the total number should not be less than eight). The fill rate was calculated for each hole, and the arithmetic mean was taken as the average fill rate of the sample. At the same time, the presence of defects such as bubbles, voids, or discontinuous filling was observed in the high-magnification SEM image.
[0130] Evaluation criteria: Average fill rate ≥ 95%, and no visible bubbles or gaps in the high-magnification SEM image, and the fill is continuous.
[0131] The results are shown in Table 5 below: Table 5. Average filling rate test results of cured adhesive film materials under different formulations and processes (n=8)
[0132] Note: Compared with Examples 1-4, the average filling rate of the cured adhesive film material in Comparative Examples 1-3 was significantly different. p <0.05). In the comparative example group 4, template contamination and graphic defects occurred during the actual imprinting process, while the templates of the other experimental groups were free of contamination and graphic defects.
[0133] It can be seen from Table 5 above: In Examples 1-4, the average filling rate of the cured adhesive film material was in the range of 95.5%-98.4%. SEM observation showed no bubbles or voids, and the filling was continuous, meeting the judgment criteria.
[0134] In the two comparative groups where methacrylate-modified tetrapod CdSe quantum dots were used instead of polymerizable ligand-modified tetrapod CdSe quantum dots, the average fill rate of the cured film was (85.1±2.5)%. SEM observation showed a small number of bubbles, no voids, and continuous filling, which did not meet the judgment criteria. This may be because the low polymerization activity of methacrylate ligands prevented the tetrapod CdSe quantum dots from effectively bonding to the crosslinking network, resulting in uneven film curing shrinkage and the formation of microbubbles in some areas, hindering the full filling of the colloid in the deep pores. Therefore, the high reactivity of polymerizable ligand-modified tetrapod CdSe quantum dots is a key factor in achieving a high fill rate.
[0135] In Comparative Example 1, which lacked polymerizable ligand-modified tetrapod CdSe quantum dots, and Comparative Example 3, which replaced polymerizable ligand-modified tetrapod CdSe quantum dots with nano-SiO2, the average filling rates of the cured film materials were (81.7±2.4)% and (77.2±2.3)%, respectively. SEM observation showed obvious bubbles and voids in both groups, and the filling was discontinuous, failing to meet the judgment criteria. This may be because the lack of polymerizable ligand-modified tetrapod CdSe quantum dots increased the curing shrinkage rate of the system, causing the film to detach from the pore walls during curing, forming voids. Simultaneously, the lack of stress buffering by nanoparticles made it difficult for bubbles to escape, leading to a decrease in filling rate. Furthermore, the lack of organic modification on the surface of nano-SiO2 resulted in severe aggregation in the resin, forming micron-sized aggregates that blocked the pore openings and prevented the colloid from entering the bottom of the pores, also causing a significant decrease in filling rate. Therefore, polymerizable ligand-modified tetrapod CdSe quantum dots, by inhibiting shrinkage, improving flowability, and eliminating aggregation, are essential components for ensuring complete filling of high aspect ratio structures.
[0136] In the four comparative groups without visible light irradiation, the average fill rate of the cured adhesive film material was (86.0±2.6)%. SEM observation showed a small number of bubbles, no voids, and blurred edges of the pattern, failing to meet the judgment criteria. This may be due to the lack of visible light post-curing, resulting in an incomplete cross-linking network and insufficient cohesive strength in the adhesive film after UV primary curing. During demolding, the adhesive film in the deep-pore structure was partially pulled out due to weak cohesion, leading to a decrease in filling depth (manifested as a low fill rate). Simultaneously, unreacted oligomers and free radicals migrated to the edges of the pattern, causing edge blurring. Therefore, post-curing is a key factor in ensuring filling integrity and pattern clarity.
[0137] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A nanoimprint adhesive for electronic semiconductor manufacturing, characterized in that, Contains the following ingredients by weight: 40-60 parts of crosslinkable resin containing double bonds; 8-20 parts of polymerizable ligand-modified semiconductor quantum dots; 15-40 parts of reactive diluent; 1-5 parts of photoinitiator; 10-25 parts organic solvent.
2. The nanoimprint adhesive as described in claim 1, characterized in that, The polymerizable ligand-modified semiconductor quantum dots comprise: Semiconductor quantum dots, and Polymerizable ligands covalently bonded to their surface.
3. The nanoimprint adhesive as described in claim 2, characterized in that, The general structural formula of the polymerizable ligand is as follows: CH2=C(CH3)-C(O)-O-(CH2) n -Se-Se-(CH2) m -SH; Where n = 2 - 6, m = 2 - 6, and n and m are both integers.
4. The nanoimprint adhesive as described in claim 2, characterized in that, The semiconductor quantum dot is a four-legged quantum dot.
5. The nanoimprint adhesive as described in claim 1, characterized in that, The crosslinkable resin containing double bonds is selected from at least one of bisphenol A epoxy acrylate and phenolic epoxy acrylate; the reactive diluent is an acrylate reactive diluent; the organic solvent is selected from at least one of alcohol ether organic solvents, ester organic solvents and ketone organic solvents; the photoinitiator is selected from at least one of acylphosphine oxide photoinitiators, α-hydroxy ketone photoinitiators, α-amino ketone photoinitiators, aromatic ketone photoinitiators and thioxanthone photoinitiators.
6. A method for preparing nanoimprint adhesive for electronic semiconductor manufacturing, characterized in that, Includes the following steps: S1. Preparation of polymerizable ligand-modified semiconductor quantum dots; S2. Under light-protected conditions, the polymerizable ligand-modified semiconductor quantum dots from step S1 are ultrasonically dispersed in an organic solvent to form a quantum dot pre-dispersion. S3. Add crosslinkable resin containing double bonds, reactive diluent and photoinitiator sequentially to the quantum dot predispersant formed in step S2, stir and mix evenly; after vacuum degassing and filtration, obtain nanoimprint adhesive.
7. The preparation method according to claim 6, characterized in that, The method for preparing polymerizable ligand-modified semiconductor quantum dots is as follows: Oleic acid-terminated semiconductor quantum dots were dispersed in anhydrous ethanol under an inert gas atmosphere. The pH of the system was adjusted to 5.0-6.5, polymerizable ligands and antioxidants were added, and the reaction was carried out at 50°C in the dark for 12-24 hours with stirring. After precipitation with acetone, centrifugation, redispersion and purification with toluene, and vacuum drying, polymerizable ligand-modified semiconductor quantum dots were obtained.
8. The preparation method according to claim 7, characterized in that, The mass ratio of semiconductor quantum dots to polymerizable ligands is 100:(3-8); the amount of antioxidant added is 0.01wt.%-0.1wt.%.
9. The preparation method according to claim 7, characterized in that, The antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, 4,4'-butylene-bis(6-tert-butyl-3-methylphenol), antioxidant 1726, and antioxidant 1010.
10. The application of the nanoimprint adhesive prepared by the preparation method according to any one of claims 6-9 in electronic semiconductor manufacturing.
Citation Information
Patent Citations
Ligand selection and exchange method of quantum dots
CN120025812A